2013
DOI: 10.1016/j.irbm.2012.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale optical flow computation from the monogenic signal

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. AbstractWe have developed an algorithm for the estimation of cardiac motion from medical images. The algorithm exploits monogenic signal theory, recently introduced as an N-dimensional generalization of the analytic signal. The displacement is computed locally by assuming the conservation of the monogenic phase over time. A local affine displacement model replaces the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The three elements can be computed via convolutions by quadrature filters, yielding a linear feature vector, [11], [26], [33], tuned to a fixed scale. The resulting phase does not coincide with the FT phase if a dominant direction cannot be computed, [1]. By contrast, phase interpretation provided by narrow bandwidth Gabor filters coincides with that of the FT phase even if the input signal is not linearly symmetric.…”
Section: Introductionmentioning
confidence: 86%
“…The three elements can be computed via convolutions by quadrature filters, yielding a linear feature vector, [11], [26], [33], tuned to a fixed scale. The resulting phase does not coincide with the FT phase if a dominant direction cannot be computed, [1]. By contrast, phase interpretation provided by narrow bandwidth Gabor filters coincides with that of the FT phase even if the input signal is not linearly symmetric.…”
Section: Introductionmentioning
confidence: 86%
“…First, the extraction of orientation maps using the monogenic signal is not done in a pixelwise way. Instead, a more robust approach based on the maximization of the directional Hilbert transform response averaged over a local neighborhood is used [12,13]. In [12] it is shown that the solution of this optimization is equivalent to the pixelwise result if the local neighborhood considered reduces to one pixel.…”
Section: Proposed Flow Estimation Methodsmentioning
confidence: 99%
“…In addition to speckle tracking algorithms, which track motion by some measure of similarity like cross Brandon Rebholz bpr5072@psu.edu 1 School of Electrical Engineering and Computer Science, The Pennsylvania State University, University Park, PA, USA correlation, there are other methods of estimating motion in ultrasound. Optical flow methods [6,7] are one of these alternatives for speckle tracking. Optical flow methods estimate displacement by a function of the gradients in either the spatial or temporal domain; however, the results are inaccurate when the displacement is large relative to the resolution of the image.…”
Section: Introductionmentioning
confidence: 99%